PENGARUH PENERAPAN MODEL EEK PADA PEMBELAJARAN PGL TERHADAP HASIL BELAJAR SISWA KELAS VIII SMPN 1 JONGGAT - Sakti, Agung purnama; Sripatmi, Sripatmi; Lu’luilmaknun, Ulfa; Turmuzi, Muhammad (Mandalika Mathematics and Educations Journal, 2024)
This research aims to determine whether there is an influence of the exploration, elaboration and confirmation (EEK) model in learning straight line equations on the learning outcomes of class VIII students at SMPN 1 Jonggat in the 2023/2024 academic year. This Quasi Experimental Research was designed using a post-test only non-equivalent control group design. The population in this study were all class VIII students at SMPN 1 Jonggat for the 2023/2024 academic year. Two classes were chosen as samples, namely class VIII B as the experimental class and class VIII A as the control class. The instruments used in this research were student learning outcomes tests (post-test), RPP, LKPD and observation sheets. The analysis technique used is parametric statistics with the result t_count = 5.93 > t_(table ) = 2.00 which shows that there is a difference in the average learning outcomes of the experimental group and the control group. Where the average learning outcomes of the experimental group are higher than the average learning outcomes of the control group. The effect size test results obtained a d value of 1.5 with high criteria. So it can be concluded that there is a high influence in the use of exploration, elaboration and confirmation models on the learning outcomes of class VIII students at SMPN 1 Jonggat.